Quadratic residues of the norm group in sectorial domains - Balyas, L.; Varbanets, P. (Algebra and Discrete Mathematics, 2016)
In the article the distribution of quadratic residues in the ring Gpn, in the norm subgroup En of multiplicative group G∗pn, is investigated. The asymptotic formula for the number R(x,ϕ) of quadratic residues in the sectorial domain of a special form has been constructed.